Joint Responsibility in Facing Financial Risks in Cooperative Groups (Case in Study Indonesian it is called Tanggung Renteng) - Wulandari Harjanti; Iwang Suwangsih; Sumiati Sumiati; Magdalena Cisilia (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
Cooperatives will exist if they can develop flexible business activities oriented to service to members, in line with the development of members' businesses, and transaction costs between members and cooperatives are smaller than non-cooperative members and are able to develop the capital base of the members themselves. There are important things that must be considered in this regard, many experiences show that one of the factors causing the weakness of cooperatives is that the excess value of capital turnover in the cooperative system is more accepted by institutions outside the cooperative and its members. Cooperation activities must be by the characteristics of the community and its members. This study aims to analyze the joint responsibility of cooperative groups in Surabaya to face financial risks. The research method used is a case study on the Setia Bhakti Savings and Loan Cooperative Surabaya. Data was collected through interviews, observations, and documentation. The study results show that the Setia Bhakti Surabaya Savings and Loan Cooperative, whose members are majority women, interprets joint responsibility as diversity that is responsible for each member with risks that must be overcome together. In the current socio-cultural order of society, it can be concluded that cooperatives must be able to grow, develop, and at the same time also play a role and benefit the life of the community that develops from the traditional society with strong sociological ties through primary emotional relationships towards a heterogeneous society and is increasingly involved in the market and capital system. This is what is found in the Setia Bhakti Surabaya Savings and Loan Cooperative, whose members are dominated by women and shared responsibility is interpreted as diversity that is responsible for each member with risks that must be overcome.